Timeliness of Reporting Finance: Dupont Analysis of Cyclical Sector Companies in Indonesia - Anggita Nurfaiza; Mira; Nurlina (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Accuracy​ time publishing report finance is aspect important in guard relevance and quality information finance in the capital market, but delay in reporting Still often occurs, especially in companies in the sector cyclical in Indonesia. Research This aim For analyze difference performance finance between the issuing company report finance appropriate time and what not, using DuPont five- factor analysis approach. Secondary data in the form of report finance annual analyzed use statistics descriptive and Spearman correlation test , equipped with with inspection relevance economics. Research results show that the issuing company report his finances appropriate time own performance more finances​ good, as reflected than the average Return on Equity (ROE) which is higher tall compared to with late company​ in report report his finances. All DuPont Analysis components found own significant relationship​ with ROE, where Operating Profit Margin and Total Asset Turnover are related positive , while Tax Burden, Interest Burden, and Equity Multiplier relate negative. Findings This confirm that accuracy time reporting finance close relation with health and stability performance finance something company .